Co‐design of memorized controllers for global sampled‐data stabilization a class of nonlinear system with input delay - Kecai Cao; Chunjiang Qian; Shihua Li; Juping Gu (IET Control Theory & Applications, 2023)
Abstract Global sampled‐data stabilization for a class of nonlinear continuous system with input delay has been investigated directly in the discrete‐time domain due to challenges confronted in dealing with infinite‐dimensional system under input delay. Memorized state feedback controllers and output feedback controllers based on dynamic extension of state space have been constructed within the framework of co‐design between sampling period and scaling gain. Upon this compensation scheme, global sampled‐data stabilization a class of nonlinear system has been successfully realized no matter the input delay is smaller than the sampling period or not. Compared with memory‐less sampled‐data controllers, not only sampled‐data stabilization under large input delay has been realized but also transient performance of closed‐loop system has been further improved. Simulation results under different input delays and sampling periods have illustrated the effectiveness of results obtained.